Impact of ChatGPT on learners in a L2 writing practicum: An exploratory investigation - Yan, Da (Education and information technologies, 2023)
Technology-enhanced language learning has exerted positive effects on the performance and engagement of L2 learners. Since the advent of tools based on recent advancement in artificial intelligence (AI), educators have made major strides in applying state-of-the-art technologies to writing classrooms. In November 2022, an AI-powered chatbot named ChatGPT capable of automatic text generation was introduced to the public. The study tried to apply ChatGPT’s text generation feature in a one-week L2 writing practicum. The study adopted a qualitative approach to investigate students’ behaviors and reflections in their exposure to ChatGPT in writing classrooms. The developmental features in learning activities and reflective perceptions were triangulated for the piloting evaluation of the impact of ChatGPT on L2 writing learners. The findings revealed the affordance and potential applicability of the tool in L2 writing pedagogy. Additionally, the tool also showcased an automatic workflow that could maximize the efficiency in composing writing. However, participants generally expressed their concern with its threats to academic honesty and educational equity. The study impelled the reconceptualization of plagiarism in the new era, development of regulatory policies and pedagogical guidance to regulate proper utilization of the tool. Being a pioneering effort, the study accentuated future research directions for more insights into the application of ChatGPT in L2 learning, and the establishment of corresponding pedagogical adjustments.